1994
DOI: 10.3109/10826089409047918
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Theory of Reasoned Action to Predict Drug and Alcohol Use

Abstract: The present study examines the role of self-esteem (SE) in the prediction of drug and alcohol use. Consistent with research on the theory of reasoned action, we suggest that alcohol and drug attitudes and subjective norms are more useful in the prediction of self-reported drug and alcohol consumption than SE. In the present study, measures of SE, drug attitudes, subjective norms, and drug use behaviors were collected from 2,074 high school and college students. Results indicate that drug attitudes and subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 11 publications
3
32
0
1
Order By: Relevance
“…Our study showed that another anticipant is social norms, and Laflin et al showed norms have anticipant effects on drug abuse (10).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our study showed that another anticipant is social norms, and Laflin et al showed norms have anticipant effects on drug abuse (10).…”
Section: Discussionsupporting
confidence: 64%
“…Morrison et al showed that attitude is the most important anticipant of intention to use marijuana in young women (9). Laflin et al showed that attitude is an important anticipant for drug abuse (10). Therefore, changing adolescent attitude towards drug abuse can be a proper solution in this field and it is, also, necessary to consider the emotional field in specific educational programs of preventing hazardous behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Given the long-established relationship between positive attitude toward substance use and actual substance use (Martino & Truss, 1973;Champion & Bell, 1980;Kandel, 1980;Barber & Grichting, 1987;Eiser, Eiser, Gammage, & Morgan, 1989;Laflin, Moore-Hirschl, Weis, & Hayes, 1994) research utilising attitudinal measures, assessing sensitive topics such as substance-related issues, may be more reliable and attract more truthful responses than self-reported behaviours. This is evidenced by the clear and consistent patterns of relationship reported by empirical studies exploring the connection between explicit religion and negative attitudes toward substances (utilising the same or similar measures).…”
Section: Religion and Substancesmentioning
confidence: 99%
“…Whereas social norms inherently refer to the behavior of groups (Ahern et al, 2008), drinking norms are typically measured by the perception of the norm among individuals in the group, with strong associations between perception of permissive norms and increased alcohol use and AUDs (Borsari and Carey, 2001;Caetano and Clark, 1999;Chawla et al, 2007;Greenfi eld and Room, 1997;Lafl in et al, 1994;Lewis et al, 2010). Efforts to change social norms related to substance use can have a substantial public health impact (e.g., the notable decreases over time in tobacco use through public education) (Emery et al, 2005;Farrelly et al, 2005).…”
mentioning
confidence: 99%